1995
DOI: 10.1007/bf00401832
|View full text |Cite
|
Sign up to set email alerts
|

Insulinoma cells in culture show pronounced sensitivity to alloxan-induced oxidative stress

Abstract: SummaryIn a model system of cultured J-774 cells we have previously shown that alloxan in moderate concentrations is toxic only in the presence of a reducing agent with the production of hydrogen peroxide. The cytotoxicity was found to involve lysosomal destabilization. In the present study the cytotoxic effects of (i) alloxan alone, (ii) a combination of alloxan and cysteine or (rio hydrogen peroxide were investigated in two established insulinoma cell lines (HIT-T15 and RINm5F), and compared with the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 32 publications
6
25
0
1
Order By: Relevance
“…In cells, SOD catalyzes the conversion of O 2 -to H 2 O 2 , and H 2 O 2 is further reduced to H 2 O by the activity of CAT or GSH-px. Pancreatic β cells have been reported to contain low levels of endogenous antioxidant enzymes, particularly GSH-px and CAT (27). In the present study, SIN-1-treated HIT-T15 cells were shown to have decreased GSH-px and CAT activities, which may be due to the increased oxidative damage induced by SIN-1.…”
Section: Discussionsupporting
confidence: 42%
“…In cells, SOD catalyzes the conversion of O 2 -to H 2 O 2 , and H 2 O 2 is further reduced to H 2 O by the activity of CAT or GSH-px. Pancreatic β cells have been reported to contain low levels of endogenous antioxidant enzymes, particularly GSH-px and CAT (27). In the present study, SIN-1-treated HIT-T15 cells were shown to have decreased GSH-px and CAT activities, which may be due to the increased oxidative damage induced by SIN-1.…”
Section: Discussionsupporting
confidence: 42%
“…1.5 min. at neutral pH and 37°C in physiological solutions (Zhang et al 1995), it is reported to generate both extra-and intra-cellular ROS (free radicals), which are responsible for its toxic effect. ALX is extracellularly reduced to dialuric acid through interaction with any available cysteine, GSH or sulfhydryl group at the extracellular plasma membrane sites, followed by the auto-oxidation of dialuric acid back to ALX resulting in redox-cycling.…”
Section: Discussionmentioning
confidence: 99%
“…ALX is extracellularly reduced to dialuric acid through interaction with any available cysteine, GSH or sulfhydryl group at the extracellular plasma membrane sites, followed by the auto-oxidation of dialuric acid back to ALX resulting in redox-cycling. This is accompanied by superoxide anion radicals (O 2 Á) and hydrogen peroxide (H 2 O 2 ), of which the latter can diffuse into the intracellular compartment (Winterbourn and Munday 1989;Lenzen and Munday 1991;Zhang et al 1995;Szkudelski 2001). Other studies have suggested that the basis for the toxicity of ALX to pancreatic b-cells is that it is taken up into the cells via the Glut 2 glucose transporter, where it is reduced to dialuric acid by intracellular cysteine and/or GSH (Elsner et al 2002(Elsner et al , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Because islet cells and insulinoma cells possess only low concentrations of oxygen free-radical scavenging enzymes (Oberley, 1988), their cellular function is easily damaged (Burkart et al, 1992;Mandrup-Poulsen et al, 1990;Zhang et al, 1995). The highly reactive hydroxyl radical ( • OH) is generated via the iron mediated Fenton reaction (Cross et al, 1987) from the superoxide anion radical ( • O2) and hydrogen peroxide (H2O2), which is known to be produced in pancreatic islets by STZ or ALX (Takasu et al, 1991;Wilson et al, 1984).…”
mentioning
confidence: 99%